2014
DOI: 10.1007/s00431-014-2326-2
|View full text |Cite
|
Sign up to set email alerts
|

Infant locomotive development and its association with adult blood pressure

Abstract: These results highlight the positive sequelae of advanced locomotive development during infancy, suggesting that the common regulatory systems between locomotion and blood pressure may influence the development of raised blood pressure over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The information on motor, social and lingual development of the children was gathered in regular visits to the Finnish child welfare clinics by nurses and doctors interviewing the parents and observing the children during infancy and early childhood in monthly intervals [32] . This is a normal procedure in Finnish public health care and was not organized particularly for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The information on motor, social and lingual development of the children was gathered in regular visits to the Finnish child welfare clinics by nurses and doctors interviewing the parents and observing the children during infancy and early childhood in monthly intervals [32] . This is a normal procedure in Finnish public health care and was not organized particularly for this study.…”
Section: Methodsmentioning
confidence: 99%
“…This is a routine procedure in Finnish public health care, and the protocol was not organized for study purposes. Thereafter, the data were retrospectively completed as previously described 18 . The following milestones were addressed: making sounds, holding up the head, grabbing objects, turning from back to tummy, sitting without support, standing with support, walking with support, standing without support, and walking without support.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the Northern Finland Birth Cohort 1966 (NFBC) revealed several age‐specific relationships. Infant motor development was associated with sports participation in adolescence, 12 as well as physical performance 17 and blood pressure 18 in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Independent walking, or upright and bipedal walking, a unique distinction of the human species, is the major motor developmental task during the first two years of life [ 33 ]. Age at onset of walking has often been used as an indicator of the progress of motor development in early life [ 14 , 17 ] and been shown to be associated with health risks in later life, such as bone strength [ 34 ] and blood pressure [ 35 ]. The age at which a child first walks independently varies widely from person to person and typically ranges from 8 months to 17–18 months, while 2.7% of children were not be able to walk independently at 24 months in a healthy sample [ 22 ].…”
Section: Discussionmentioning
confidence: 99%